Navigating vulnerable community-based urban heat adaptation under SDG 11 - Xiaolin Lao; Aura-Luciana Istrate; Francesco Pilla (npj Urban Sustainability)
Abstract Exacerbated by climate change, the increasing urban heat is a silent disaster especially affecting vulnerable communities representing a city’s weakest part. To assess vulnerabilities and understand the local urban heat experiences, this study employed reconnaissance and resident surveys across diverse vulnerable community types (formal and informal settlements) in Xi’an, China. Along with a policy disconnection from residents’ needs, results indicate that heat-coping resources are largely unavailable, and community engagement is limited. Structural equation modelling indicates that while community-based governance reduces socio-economic pressure, it does not significantly improve services or awareness. Governance effectiveness and policy urgency varied not only across communities but also within communities as influenced by housing types: they were stronger within urban villages and gated commercial housing, whereas shantytowns faced heightened vulnerability. The study advocates a community-based approach to identify and address specific vulnerabilities, as well as align residents’ needs with policy contributing to SDG 11 sub-targets.